Perancangan Tata Letak Fasilitas Departemen Hand Add di PT. X - Juan Exel Sandjaja; Tanti Octavia (Jurnal Titra, 2020)
PT. X is a company that engaged in the animal feed manufacturing. PT. X had started to produce animal feed since 1972. Animal feed that produced by PT. X includes chicken, pork, duck, quail, and etc. The form of animal’s feed is flours, pellets and crumbles. Now, one of  PT. X has department, The Hand Add Department, has a problem that the layout still cause a lot of time for workers to move during the work process. A lot of time is wasted because there is a backtracking movement. The Hand Add Department also has a plan to add a special scale for weighing a special material. That is called anti-cocci. The facility layout design and the additional of a special scale for weighing a special material after the experiment has resulted in saving distance between facilities about 14,75%, saving working time/day about 24,99%, saving time for one batch mixing about 8,26%.